Assessment of the On-Board Energy Storage Parameters of the Locomotive for Rail Quarry Transport - Riabov, Ievgen; Kondratieva, Liliia; Overianova, Liliia; Goolak, Sergiy (Springer Nature Switzerland AG, 2022)
The use of on-board energy storage on a locomotive for rail quarry transport is considered. Three scenarios of energy consumption in the power supply of traction electric drive and auxiliary locomotive systems using on-board energy storage system (OESS) are considered. For each of the scenarios, simplified mathematical models of processes have been developed, which describe the energy exchange in the traction and auxiliary systems during exploitation of OESS. The input data for the calculations are the dependence of the power at wheel of locomotive on time, which is determined by the results of solving the traction task for the section railway line. Calculations has been made for the studied scenarios of OESS operation using data of locomotive operation at PJSC “Poltava Ferrexpo Mining”. It is defined that the parameters of OESS depend on the energy consumption scenario. It is proposed to use OESS on the locomotive with electric traction drive based on induction motors for PJSC “Poltava Ferrexpo Mining” according to energy consumption scenarios, which provide power from OESS during shunting and power from OESS when shunting with co-powered from the catenary for guide lifts.
Keywords: rail quarry transport; electric traction system; on-board energy storage; traction asynchronous electric drive